Detection of deformation anisotropy of tuff by a single triaxial test on a single specimen. (August 2018) - Togashi, Yota; Kikumoto, Mamoru; Tani, Kazuo; Hosoda, Koichi; Ogawa, Koji
Abstract: Rock anisotropy has conventionally been determined by numerous tests using many specimens sampled at several orientations, however, it is both costly and time consuming. The anisotropic deformation properties (transversely isotropic elasticity and its dominant orientation) of a tuffaceous rock sample obtained in Utsunomiya city, Japan, and characterized by a clear bedding plane, were determined by a newly proposed method, namely, a single triaxial test using a single specimen. Using this method, the dominant orientations of anisotropy are determined by the principal orientations of the strain during isotropic consolidation, and the elastic parameters can be determined by stresses and strains during triaxial compression. This method required the implementation of a triaxial testing apparatus with a newly designed cap including a slider mechanism and low-friction sheets. The six components of the symmetrical, small strain tensors of the tuff specimen were measured using nine strain gauges, while the 3D principal strains were evaluated during uniaxial and consolidated drained triaxial tests. To verify the proposed method, the anisotropic properties of four specimens sampled from a cubic block at different orientations, as characterized by the proposed method, were compared with those determined by multiple uniaxial tests using the specimens sampled for different orientations. The strain responses of the uniaxial tests demonstrated that the Young's modulus of the tuff in the bedding orientation is 1.5 times greater than that for the perpendicular orientation. The orientation of the principal strains deviate from the loading orientation due to the orientation of the bedding plane, and the orientations during isotropic consolidation were inclined in accordance with the dip orientation of the bedding plane. Similar values were evaluated for each anisotropic property determined by both a single triaxial test on each specimen and multiple uniaxial tests. The obtained values demonstrated that the Young's moduli for the bedding orientation are 1.5–2.7 times larger than that in the perpendicular orientation. Highlights: Deformation anisotropy of tuff with bedding plane detected by single triaxial test. New low-friction cap with slide mechanism is used at top and bottom of specimen. Proposed method and advantages verified through triaxial tests on tuff. Young's moduli in bedding and perpendicular orientation vary by factor of 1.5–2.7.